2018
DOI: 10.1002/jcph.1336
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Adverse Drug Reactions–Nationwide Active Surveillance Network: Canadian Pharmacogenomics Network for Drug Safety Database

Abstract: Adverse drug reactions (ADRs) are a major problem in modern medicine, representing up to the fourth-highest cause of mortality. Pharmacogenomic tests are 1 of the most promising methods to tackle the challenge of ADRs. The objective of this study was to analyze the clinical and demographic information of the pan-Canadian active surveillance network, Canadian Pharmacogenomics Network for Drug Safety (CPNDS). Information entered into the database by trained active surveillors between May 15, 2005 and May 9, 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Ototoxicity is one of the most commonly reported adverse drug reactions 1 . Symptoms of ototoxicity, such as hearing loss and vestibular dysfunction, profoundly impact quality of life and are a public health burden.…”
mentioning
confidence: 99%
“…Ototoxicity is one of the most commonly reported adverse drug reactions 1 . Symptoms of ototoxicity, such as hearing loss and vestibular dysfunction, profoundly impact quality of life and are a public health burden.…”
mentioning
confidence: 99%
“…The individuals carrying nonactive alleles are classified as “predicted” poor metabolizers with no metabolic capacity for these enzymes. On the contrary, individuals with more than two active alleles have been associated with increased enzyme activity [14]. There are two risk scenarios in regards to the genetic background: the first is the administration of a prodrug that requires conversion to an active metabolite where slow metabolizers generate loss of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Our population exhibited variability in CNVs: 50% of individuals carried deletions and duplications while 39% had a unique type of CNV (deletion or duplication). According to the number of CYP-450 or GST active copies, the individuals can be potentially defined as poor metabolizers (PM) or ultrarapid metabolizers (UM) [14]. We identified that 83% of the analyzed individuals presented CNVs in one or several of the CYP-450 and / or GST genes studied.…”
Section: Introductionmentioning
confidence: 99%
“…A strong recommendation (level A) is expected to be chosen by a majority of informed healthcare providers and patients. A recommendation in the category "Moderate" is expected to require individualized informed decision making by patients and healthcare providers (Ross et al, 2010;Amstutz et al, 2014;Tanoshima et al, 2019).…”
Section: Canadian Pharmacogenomics Network For Drug Safetymentioning
confidence: 99%
“…The DPWG has adopted "normal metabolizer" (NM) for CYP2D6, CYP2C19, CYP3A4, CYP1A2, CYP2B6, TPMT, and NUDT15 (The Dutch Pharmacogenomic Working Group, 2020b). The CPNDS also used "normal metabolizer" in its guideline on tamoxifen (Tanoshima et al, 2019). However, for CYP3A5 the DPWG decided to maintain the phenotype terminology, "CYP3A5 non-expressor," for carriers of two nonfunctional alleles (CYP3A5*3/*3), "CYP3A5 heterozygous-expressor" and "CYP3A5 homozygous-expressor."…”
Section: Terminology Of Predicted Phenotypesmentioning
confidence: 99%